BDH1 promotes lung cancer cell proliferation and metastases by PARP1‐mediated autophagy. Issue 7 (15th March 2023) - Zhang, Zhimin; Bi, Xin; Lian, Xiaojuan; Niu, Zhongxi
Abstract: Lymph node metastases and distant metastases were the important limiting factor for therapy of unresectable locally advanced (IIIB stage) and oligotransduction (IVa stage) lung cancer. This study was undertaken to identify a novel predictive biomarker for predicting lymph node metastases of lung cancer. A total of 364 patients with lung cancer which comprised of 198 patients with transcriptome sequencing data, 110 cases with immunohistochemistry data and 66 patients with serum samples were included to identify and validate the candidate gene. Autophagy was measured by western blots, immunofluorescence and electron microscope. We found that 3‐hydroxybutyrate dehydrogenase 1 (BDH1) was associated with proliferation and metastases of lung cancer. BDH1 expression in both tissue and serum samples was associated with lung cancer metastases. Mechanical studies revealed that the AMPK‐mTOR signalling pathway mediated by PARP1 played an important role in BDH1‐induced autophagy. Activation of mTOR pathway markedly increased the effect of BDH1 in cell proliferation and metastases. These results were verified by the knockdown of PARP1. Furthermore, in vivo administration of BDH1 effectively promoted tumour growth in H460 xenografts mice. Our finding not only suggested that BDH1 might be useful as a novel biomarker and therapeutic target for lung cancer metastases, but also imply that PARP1‐mediated AMPK‐mTOR signalling pathway might play a critical role in BDH1‐induced autophagy and lung cancer proliferation and metastases.